Antioxidant Activity of Ethanol and Methanol Extracts of Black Turmeric (Curcuma Caesia Roxb.) Using the DPPH (2,2-Diphenyl-1-Picrylhidrazyl) Method - Ni nyoman wahyu udayani; Ketut Agus Adrianta; IGAA Kusuma Wardani (Science Midwifery, 2022)
Free radicals are highly reactive compounds in the body that can cause degenerative diseases. One mechanism that can counteract free radicals is antioxidants. Natural antioxidants can be obtained from traditional drinks made from plants that contain active antioxidant compounds such as black turmeric (Curcuma caesia Roxb.) from the Zingiberaceae family. This study aims to determine the antioxidant activity of black turmeric extract. Before testing the antioxidant activity, qualitative and quantitative analysis were carried out. Qualitative analysis was carried out by phytochemical screening. The antioxidant activity of black turmeric extract was tested using the DPPH method. This test begins with the manufacture of extracts and preparation of test samples, then measurement of free radical scavenging activity using a UV-Vis spectrophotometer is carried out. Based on the results of the percentage measurement, the linear regression equation for the ethanol extract was obtained, namely y = 0.1526x + 0.9105 and the value of R2 = 0.9965, and for the methanol extract, namely y = 0.2376x + 1.6809 and the value of R2 = 0.996. According to the linear regression equation, black turmeric extract has antioxidant activity, which is categorized as a very weak antioxidant with an IC50 of 321,687 ppm for ethanol extract and 203, 363 ppm for methanol extract.